Structure design study of vacuum magnetic fluid seal - Sijia Liu; Decai Li; Decai Li; Xinzhi He; Zhili Zhang (Frontiers in Materials, 2022)
In response to the requirement of high vacuum and leakage rate of a small-diameter low-speed device of an enterprise, a double magnet multistage magnetic fluid sealing device is designed by analyzing the advantages and disadvantages of four different vacuum magnetic fluid sealing devices. The Ansys simulation software is used to analyze and calculate the magnetic field strength and distribution of this magnetic fluid sealing device, discuss the influence of the number of intermediate section pole teeth and the seal gap size on the pressure resistance of the magnetic fluid seal, and summarize the law. The proposed structure of the double magnet multistage magnetic fluid sealing device is optimized and determined by the influence law of structural parameters. Compared with traditional sealing forms, the advantages of the sealing device proposed in this article can be summarized as low processing difficulty, good reliability, and high pressure resistance. The reliability and rationality of this magnetic fluid sealing device are demonstrated by Ansys simulation results, which provide a reference for the structural design and analysis of small-diameter low-speed vacuum magnetic fluid sealing devices.